Mutilation and theft of library materials in college and university libraries in Region I - Pojas, Elvira Quileban C. (1990)
The primary purpose of this study is to identify factors which cause mutilation and theft of library materials in forty-two college and university libraries in Region I. It covers detailed aspects such as the extent of mutilation and theft, factors that influence mutilation and theft, and methods of preventing mutilation and theft of library materials in the libraries of Region I.